Structural plasticity of pyramidal cell neurons measured after FLASH and conventional dose-rate irradiation - Dara L. Dickstein; Richard Zhang; Ning Ru; Marie-Catherine Vozenin; Bayley C. Perry; Juan Wang; Janet E. Baulch; Munjal M. Acharya; Charles L. Limoli (Brain Structure and Function, 2025)
Evidence shows that ultra-high dose-rate FLASH-radiotherapy (FLASH-RT) provides relative protection against normal tissue complications and functional decrements in the irradiated brain. Past work has shown that radiation-induced cognitive impairment, neuroinflammation and reduced structural complexity ofgranule cell neurons were not observed to the same extent after FLASH-RT (> MGy/s) compared to conventional dose-rate (CONV, 0.1 Gy/s) delivery. In this study, we explored the sensitivity of hippocampal CA1 and medial prefrontal cortex (mPFC) pyramidal neurons to cranial irradiation and dose-rate modulation using electron and confocal microscopy. Neuron ultrastructural analyses by electron microscopy after 10 Gy FLASH- or CONV-RT exposures indicated that irradiation had little impact on dendritic complexity and synapse density in the CA1, but did increase the length and head diameter of smaller non-perforated synapses. Similarly, irradiation caused no change in mPFC prelimbic/infralimbic axospinous synapse density, but reductions in non-perforated synapse diameters. While irradiation resulted in thinner myelin sheaths compared to controls, none of these metrics were dose-rate sensitive. Analysis of fluorescently labeled CA1 neurons revealed no radiation-induced or dose-rate-dependent changes in overall dendritic complexity or spine density, in contrast to our past analysis of granule cell neurons. Super-resolution confocal microscopy following a clinical dosing paradigm (3 × 10 Gy) showed significant reductions in excitatory vesicular glutamate transporter 1 and inhibitory vesicular GABA transporter puncta density within the CA1 that were largely dose-rate independent. Collectively, these data reveal that, compared to granule cell neurons, CA1 and mPFC neurons are relatively more radioresistant irrespective of radiation dose-rate.